Bowhead Whales Along the Chukotka Coast in Autumn - Moore, Sue E.; George, John C.; Coyle, Kenneth O.; Weingartner, Thomas J. (ARCTIC, 1995)
Bowhead whales (Balaena mysticetus) were seen in autumn 1992 and 1993 only along the northern coast of Chukotka, Russia, although an extensive area of the Chukchi Sea was searched during ship cruises. Single-day counts for 76 and 50 bowheads were made on 1 October 1992 and 3 October 1993, respectively, with only a few whales seen on other days. Whales seen between Cape Schmidt and Cape Vankarem on 1 October 1992 appeared to be feeding, but there was no means to detect or sample subsurface forage that year. On 3 October 1993, bowheads appeared to be feeding in an area where a 5 m x 8 km patch of zooplankton was identified, via acoustics, at 25-30 m in water 35 m deep. A vertical-tow sample near the patch indicated the euphausiid Thysanoessa rachii, a common bowhead prey species, was abundant in the water column. The location of the zooplankton patch corresponded with a sharp salinity (proxy density) gradient. In addition, whale distribution coincided with a surface thermal boundary, identified by satellite-borne Advanced Very High Resolution Radiometer (AVHRR) imagery. The confinement of bowhead sightings to the northern coast of Chukotka in 1992-93 corresponds to reports from autumn surveys in 1979, 1980 and 1990, while the association of whales with physical oceanographic fronts is similar to findings from a study of bowhead feeding areas in the southern Beaufort Sea. These observations suggest that the Chukotka coast may be an important feeding or staging area for the Bering Sea stock and that oceanographic patterns influencing whale occurrence may be identifiable from standard oceanographic measurements.Key words: bowhead whale, Balaena mysticetus, migration, Chukchi Sea, Bering Sea, Chukotka, Thysanoessa rachii, satellite imagery, AVHRR Durant l'automne de 1992 et celui de 1993, on n'a pu observer de baleines boréales (Balaena mysticetus) que le long de la côte nord de Chukotka (Russie), bien que des recherches aient eu lieu dans une zone étendue de la mer des Tchouktches lors de croisières en bateau. Des ...